Reaksi Pasar terhadap Pengumuman Penawaran Saham Terbatas di Indonesia - Sutrisno, Bambang; Priharta, Andry (Faculty of Economic and Business, 2019)
The right issue announcement may lead the market to react and affect the stock performance. This study aims to analyze the effect of the right issue on the abnormal return. This research uses a sample of 18 firms listed in the Indonesia Stock Exchange from 2014 to 2016. This study employs one sample t test and wilcoxon test. The results show that there is no abnormal return in the days surrounding right issue announcement. The results also find that there is no difference in abnormal return between after and before the right issue announcement. This research implies that the existing stockholders and investors need to consider carefully before deciding to invest in go public companies do the right issue.